2022
DOI: 10.1039/d2ra03179e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrazolo[5′,1′:2,3]imidazo[1,5-c]quinazolin-6(5H)-ones and molecular docking study of their affinity against the COVID-19 main protease

Abstract: A novel series of fused pyrazolo[5′,1′:2,3]imidazo[1,5-c]quinazolin-6(5H)-ones were synthesized and their affinity against the COVID-19 main protease was investigated using molecular docking study and compared to that of some used clinical drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A critical assessment of docking programs and scoring functions in terms of reproducing crystallographically determined protein/ligand complex structures is available in [93]. Numerous molecular docking studies have been reported in the context of repurposing and discovering potent non-covalent and covalent inhibitors for critical proteases of the virus SARS-CoV-2 [111][112][113][114][115][116][117][118]. Some excellent reviews of this topic are given elsewhere [1,2,7,119].…”
Section: Pharmacophore-based Virtual Screeningmentioning
confidence: 99%
“…A critical assessment of docking programs and scoring functions in terms of reproducing crystallographically determined protein/ligand complex structures is available in [93]. Numerous molecular docking studies have been reported in the context of repurposing and discovering potent non-covalent and covalent inhibitors for critical proteases of the virus SARS-CoV-2 [111][112][113][114][115][116][117][118]. Some excellent reviews of this topic are given elsewhere [1,2,7,119].…”
Section: Pharmacophore-based Virtual Screeningmentioning
confidence: 99%